The impact of specific determinants on corporate bond yield spreads - МилицковаТатьяна Михайловна (Journal of Corporate Finance Research / Корпоративные Финансы | ISSN: 2073-0438, 2013)
Authors: Tatyana Militskova National Research University The Higher School of Economics The present research is devoted to the analysis of the determinants which affect the newly issued corporate bond yields. In this paper the emphasis is placed on the determinants specific for the Russian corporate bond market. The author examines Russian corporate bonds issued over the period from May 2008 to December 2012 except for the bonds issued by banks, assurance companies and other financial institutions. On the basis of these observations the author develops an econometric model which demonstrates how corporate bond yield spreads depend on issuer’s creditworthiness, issuer’s industry, bond issue parameters and aggregated indicators.